If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 13x + -61 Reorder the terms: -5 + 6x = 13x + -61 Reorder the terms: -5 + 6x = -61 + 13x Solving -5 + 6x = -61 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -5 + 6x + -13x = -61 + 13x + -13x Combine like terms: 6x + -13x = -7x -5 + -7x = -61 + 13x + -13x Combine like terms: 13x + -13x = 0 -5 + -7x = -61 + 0 -5 + -7x = -61 Add '5' to each side of the equation. -5 + 5 + -7x = -61 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = -61 + 5 -7x = -61 + 5 Combine like terms: -61 + 5 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| 2x+20=10x-52 | | 6b=66 | | 8x-15=2x+3 | | 3a-8a-4a=81 | | 5x+2y=21 | | 3x(2x-5)=0 | | h+17=-1 | | 10x+57=10x+12 | | 6(3-4x)+12=10x-2(5-3x) | | a+17=-1 | | 6x+9=2x-5 | | 5x=3x-28 | | 1-x=x+1 | | n(n+8)=0 | | 5x-3(2+3x)=6 | | 38-6x=3x+16 | | 3(x-1)=18-(5x+1) | | 9-7x=17-14x | | -24=3x-2(-x-13) | | -44-8x=9x+24 | | 143=4x+3(7x+6) | | 4x+10=-14-8x | | 3x+50=6x+14 | | 7x-(4x+9)=-37 | | 144-3x=6x+18 | | 9(a-2)+15=33 | | 3m-12=4m | | -16-3x=12-10 | | 9w-3w+2=32 | | 78-6x=8x+22 | | -2(x+6)=-3(-2x+8) | | 7z+13=3z |